Aspects of Nonverbal Communication in the Ancient Near East - Gruber, Mayer Irwin (1977)
Submitted in partial fulfillment of the requirements for the degree of Doctor of Philosophy in the Faculty of Philosophy, Columbia University; Xerox University Microfilms 77-24,095; gestures and postures of prayer, obeisance, sadness, anger etc. attested in Akkadian, Ugaritic and Hebrew literature.